The Search for the Self: the Essence of Dewey's Ethics - Teodora Pezzano (LED Edizioni Universitarie, 2013)
This paper is divided into three brief parts and will try to clarify, in the young John Dewey, the meaning of the individual as a social organism. The individual as a social organism is considered as a «container and user» of democracy, in continuous movement and thus changeable, through: (a) the understanding of ethics, an ideal that loses value if it is separated from the spiritualistic-naturalistic conception; (b) the organic law of every individual. In fact, the subjective aspect, the intention, the inner thrust all link up with the objective aspect, the universal status, with society in all its aspects; (c) the role of social theory as a peculiar type of moral organism and as a concept of individual liberty to be understood in its positive meaning: becoming social individuals. These three aspects embody, within an educational perspective, the idea of progress that consists of the common good and common duty, thus becoming the main thread of Dewey's democratic theory. By means of pedagogical dictates Dewey will prove that, in order to become a «conscious act», the creation of a State must become the representation of the individual's essence.